Women are the message. Choruses and dances of Women's Political Movement in Latin America - Pilar Amador Carretero (Feminismo/s, 2003)
Every political system carries out a socializing action that in totalitarian States is complemented by political propaganda. During Franco’s period, there is a proven evidence that the ideological contents of this regime where given through a propagandistic way which included control on the media, education and the Church. So movies, as cultural products of this society, are important tools in the definition, production and reproduction of the ideology of this period. In this essay, I analyse a movie called Ronda Española which shows the activities of the so called «Coros y Danzas de la Sección Femenina» in their trips around South America. My analysis aims at presenting close approach to the reality of falangist women and the message they wanted to transmit through this activity.